Separating content-specific retrieval from post-retrieval processing - Doidge, Amie N.; Evans, Lisa H.; Herron, Jane E.; Wilding, Edward L. (Elsevier, 2017)
According to cortical reinstatement accounts, neural processes engaged at the time of encoding are re-engaged at the time of memory retrieval. The temporal precision of event-related potentials (ERPs) has been exploited to assess this possibility, and in this study ERPs were acquired while people made memory judgments to visually presented words encoded in two different ways. There were reliable differences between the scalp distributions of the signatures of successful retrieval of different contents from 300 to 1100 ms after stimulus presentation. Moreover, the scalp distributions of these content-sensitive effects changed during this period. These findings are, to our knowledge, the first demonstration in one study that ERPs reflect content-specific processing in two separable ways: first, via reinstatement, and second, via downstream processes that operate on recovered information in the service of memory judgments.